2015
DOI: 10.1039/c5ra09507g
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of structure and electromagnetic interference shielding performance for silver nanostructure hybrid polyimide foams

Abstract: Silver nanofillers of three different shapes were synthesized: silver nanospheres (AgNSs), silver nanowires (AgNWs) and silver nanowires-silver nanoplatelets (AgNWPs). Ultra-lightweight polyimide (PI) composite foams filled with these three silver nanofillers were fabricated by a facile and effective one-pot liquid foaming process, respectively. Their microstructure, electromagnetic interference (EMI) shielding effectiveness (SE) and shielding mechanisms were investigated. It was found that, at the same nanofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 79 publications
2
60
0
Order By: Relevance
“…We attribute the effective EMI shielding of these films to the enhanced EMI absorption with the LbL film architecture and the excellent electrical conductivity of the conductive fillers (i.e., MXene and CNT). To make a shielding materials comparison among the recently reported carbon‐based[1b,4b–d,5] and MXene‐based[1a,c] with commercially available metal films (e.g., Al foil and Cu foil),[1a,2] we estimate the specific EMI shielding effectiveness (SSE/t) of the 300‐bilayer MXene‐CNT films. The SSE/t incorporates three important factors, the EMI shielding effectiveness, density, and thickness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute the effective EMI shielding of these films to the enhanced EMI absorption with the LbL film architecture and the excellent electrical conductivity of the conductive fillers (i.e., MXene and CNT). To make a shielding materials comparison among the recently reported carbon‐based[1b,4b–d,5] and MXene‐based[1a,c] with commercially available metal films (e.g., Al foil and Cu foil),[1a,2] we estimate the specific EMI shielding effectiveness (SSE/t) of the 300‐bilayer MXene‐CNT films. The SSE/t incorporates three important factors, the EMI shielding effectiveness, density, and thickness.…”
Section: Resultsmentioning
confidence: 99%
“…To efficiently reduce the electromagnetic exposure, metal (e.g., Cu and Al) is conventionally used as a shielding material, however these metallic materials are opaque, heavy, and nonflexible. [1b,c,2] Flexible transparent shielding solutions that can adapt to any geometric solution are needed to meet current market demands. Recently, carbon‐based materials, particularly carbon nanotubes (CNTs) and graphene combined with conductive polymer composites have attracted much interest for EMI shielding due to their light weight, flexibility, and processing advantages .…”
Section: Introductionmentioning
confidence: 99%
“…5d). 1,4,5,11,13,19,20,28,31,32,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] This nding is noteworthy because the LG-4 lm would satisfy several commercial requirements for an EMI shielding material, for example ultrahigh EMI SE (73.7 dB), low density (2.05 g cm À3 ), ultrathin thickness (0.014 mm), anti-corrosion, high exibility and easy fabrication.…”
Section: Morphologies Of Graphene Lmsmentioning
confidence: 99%
“…References are available in which silver in various forms has been used is polymer matrix composites for EMI SE. Ma et al [29] prepared a silver nanostructure hybrid polyimide foams with outstanding specific SE like 1208 dB g -1 cm 3 at 200 MHz, 216-249 dB g -1 cm 3 at 8-12 GHz, which far surpasses the best values of other composite materials. Yu et al [30] prepared Ag nanowires/epoxy resin composites that showed an EMI SE of 20 dB at 3-17 GHz.…”
Section: Introductionmentioning
confidence: 96%